RE-EXAMINING MILLENNIALS' INTENTION TO CONTINUOUSLY USE E-WALLET APPLICATIONS : THE ROLE OF TECHNOLOGY ACCEPTANCE MODEL (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This study aims to re-examine the Technology Acceptance Model (TAM) to explain Millennials’ intention to continously use the e-wallet applications by using Perceived Ease of Use (PEOU) and Perceived Usefulness (PU). There were 140 respondents used as sample in this study with the provision of the age limit of 20-35 years, who have e-wallet(s) account and had been using e-wallet application(s) to perform payment transaction(s). Data were collected using questionnaire. This sampling technique used was purposive sampling method and analyzed using the SPSS multiple linear regression analysis. The results of this analysis indicate that Perceived Ease of Use and Perceived Usefulness both have a significant effect towards Continuance Intention to Use e-wallet application(s) amongst Millennials. The findings of this study are important because it can be utilized as a foundation for e-wallet developers to improve technological systems with various features which focuses on enhancing consumers’ performance, furthermore this study is expected to encourage small and medium sized business to adopt fintech as one of the offered payment features.